2007
DOI: 10.1093/humrep/dem187
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between clinical examination, transvaginal sonography and magnetic resonance imaging for the diagnosis of deep endometriosis

Abstract: TVUS had better sensitivity, specificity, PPV, NPV and accuracy in cases of deep retrocervical and rectosigmoid endometriosis when compared with MRI and digital vaginal examination, confirming that it is an important preoperative examination for the definition of surgical strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
378
2
27

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 454 publications
(423 citation statements)
references
References 25 publications
16
378
2
27
Order By: Relevance
“…These results are similar to those of Guerriero et al (7), who indicated a specificity of 92% and a sensitivity of 67%, but lower than those of Abrao et al (26) and Bazot et al (5,9,(27)(28)(29). On the contrary our results are superior in terms of sensitivity compared with the data reported by Grasso et al (30) (33.3% sensitivity).…”
Section: Mri and Tg-tvus Had A Similar Diagnostic Accuracy And Good Isupporting
confidence: 90%
“…These results are similar to those of Guerriero et al (7), who indicated a specificity of 92% and a sensitivity of 67%, but lower than those of Abrao et al (26) and Bazot et al (5,9,(27)(28)(29). On the contrary our results are superior in terms of sensitivity compared with the data reported by Grasso et al (30) (33.3% sensitivity).…”
Section: Mri and Tg-tvus Had A Similar Diagnostic Accuracy And Good Isupporting
confidence: 90%
“…, 24 , 25 In the past decade, several studies have compared different imaging modalities for a role in the pre‐operative diagnosis of extra‐ovarian endometriosis. Abrao, et al compared TVS and MRI for the detection of recto‐sigmoid DIE and found that TVS had a sensitivity, specificity, and accuracy of 98%, 100%, and 99%, respectively, compared to MRI's sensitivity, specificity, and accuracy of 83%, 98%, and 90% 13 . Although MRI may have slightly higher sensitivity for uterosaccral disease, TVS performs similarly to MRI in the diagnosis of intestinal endometriosis 14 .…”
Section: Evolution Of Transvaginal Scan For Diagnosis Of Extra‐ovariamentioning
confidence: 99%
“…The MRI provides accurate information about lesions located on the upper level of the sigmoid, but for pelvic disease TVS is equally accurate and is considered the first and most widely used diagnostic tool (6,(18)(19)(20). Close communication between the radiologist or sonographer and the clinician is useful to provide the patient with accurate and adequate information regarding the extent of the disease and to plan the best possible management, whether medical, surgical, or both.…”
mentioning
confidence: 99%